Predictors of breastfeeding self‐efficacy among women attending an urban postnatal clinic, Uganda - Nankumbi, Joyce; Mukama, Ashely Atwiine; Ngabirano, Tom Denis (Nursing Open, 2019)
The aim of this study was to determine the factors associated with breastfeeding self-efficacy among postnatal women in Kampala, Uganda. This was a descriptive cross-sectional study that was conducted among women attending a postnatal clinic at a teaching hospital in Kampala. Three hundred and eighty-four postnatal women were randomly selected to respond to an interviewer-administered questionnaire. We used the Breastfeeding Self-Efficacy scale (BFSES) to assesses breastfeeding self-efficacy (BFSE). Descriptive statistics and percentages were used to summarize the findings. Bivariate and multivariate logistic regressions were used to determine predictors of BFSE. Participants had a mean BFSE score of 48.65. The 14 item BFSES consistently measured breastfeeding confidence with a Cronbach's alpha of 0.89. About six in 10 women (60.2%) had high BFSE, the rest (39.8%) had low BFSE. Having a partner (adjusted odds ratio (aOR): 13, 95% CI 3.46–15) and receiving breastfeeding support from health workers (aOR: 4.45, 95% CI: 1.95–6.12) were significantly associated with BFSE. A notable number of mothers had a low BFSE. Health workers should support breastfeeding mothers to achieve the desired exclusive breastfeeding levels.